The new Basel Capital Accord and SME financing : SMEs and the new rating culture - Ayadi, Rym.; Centre for European Policy Studies (Brussels, Belgium) (Brussels : Centre for European Policy Studies, 2005)
The First Basel Capital Accord was aimed at ensuring the stability of the international banking system. Basel II intends to strengthen the framework for dealing with credit risk. This book provides an analysis of what Basel II means for the small and medium-sized enterprise (SME) sector in Europe and its impact on its credit financing conditions. It also presents a detailed analysis of how banks formulate an internal rating system and illustrates how this system works in practice. Finally, it concludes with the key measures that should be taken by banks, SMEs, and public policymakers to improve financing in the new rating culture.
"November 2005."
Includes bibliographical references (p. 88-93).
oif 23/07/14
Loan
Keywords: Small business -- Europe -- Finance; Credit -- Europe; Bank capital -- Europe